A CASE REPORT: PHYSIOTHERAPY MANAGEMENT IN INDIVIDUAL OF PATIENT WITH PLANTAR FASCIITIS - Pramitha, Chandra Arum; Totok Budi Santoso; Kingkinnarti, Kingkinnarti (Journal of Innovation Research and Knowledge, 2023)
Plantar fasciitis is the occurrence of trauma to the fascia caused by excessive strain or pulling within the plantaris fascia resulting in microscopic tears that cause chronic inflammation. Conditions that often arise are dull and sharp pain in the heel area, pain felt at rest, moving or when pressed on the heel area in this case factors of excessive load activity, obesity, work with intensity standing for a long time are common causes. Management or Physiotherapy programs that can be given to patients with plantar fasciitis are the use of physiotherapy modalities. The purpose of this study is the success of physiotherapy management using Ultrasound, Tens, Myofascial Release, stretching and strengthening to reduce pain, increase muscle strength and increase functional ability. After physiotherapy management for 2 times a week, there was a decrease in pain levels, especially in motion pain and tenderness with T1: 4 and T3: 3 motion pain values and T1: 5 and T3: 3 press pain, an increase in muscle strength seen by the results of Manual Muscle Testing and an increase in the functional ability of the FADI index. It is expected that future studies can increase the effectiveness of the Physiotherapy program in patients with plantar fasciitis.